INISIASI GERAKAN PEDULI LINGKUNGAN PADA MASYARAKAT KELURAHAN BUKIT SARI PANGKALPINANG - Luna Febriani (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
Environment and disaster are an integral and inseparable part. In other words, environment can influence a disaster incidence in an area. Environmental issues and disasters are also urgent in Indonesian society. Apart from territorial location and demographic problems, damage and indifference to environment often present such disasters as floods, landslides, earthquakes, abrasion and so on. Flood is one of the environmental problems often occurring in Kelurahan Bukit Sari (Bukit Sari Village). This is due to the geographical conditions of Bukit Sari, located on a fairly low plain at several points and the lack of public awareness of environmental concerns. To minimize this environmental problem, the people of Kelurahan Bukit Sari have taken some efforts and movements to take care of the environment. This research is aimed at studying the environmental movements carried out by the community in order to preserve the environment. The results showed that the environmental care community movement is an initiative carried out by the community itself, while the environmental care movement consists of: waste management and sales, urban framing program and weekly mutual help or cooperative movement.